2018
DOI: 10.1080/09243453.2018.1511603
|View full text |Cite
|
Sign up to set email alerts
|

Searching for differential teacher and school effectiveness in terms of student socioeconomic status and gender: implications for promoting equity

Abstract: This paper argues that research on differential teacher and school effectiveness can be used to explore the relation between quality and equity in education. The results of secondary analyses of 2 studies concerned with effectiveness in different phases of schooling (pre-primary and primary education) are presented. These secondary analyses reveal that the socioeconomic gap in student achievement in each of the 2 core subjects (mathematics and language) tends to be smaller in classrooms and schools that are mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 69 publications
1
23
1
10
Order By: Relevance
“…The instruments on school effectiveness totalled 16 questionnaires. This instrument was adapted and developed based on the results of research on school effectiveness carried out by previous researchers (Cerit & Yıldırım, 2017;Kyriakides, Creemers, & Charalambous, 2019;Reynolds, 2018).…”
Section: Malaysian Online Journal Of Educational Management (Mojem) Imentioning
confidence: 99%
“…The instruments on school effectiveness totalled 16 questionnaires. This instrument was adapted and developed based on the results of research on school effectiveness carried out by previous researchers (Cerit & Yıldırım, 2017;Kyriakides, Creemers, & Charalambous, 2019;Reynolds, 2018).…”
Section: Malaysian Online Journal Of Educational Management (Mojem) Imentioning
confidence: 99%
“…Recent analyses and discussions have revealed that equity and quality should be connected (Garira, 2020;Kyriakides et al, 2019;OECD, 2012OECD, , 2018. Equity is not only about providing access to education: it requires also support to help students enter educational paths.…”
Section: Increasing Inequalitiesmentioning
confidence: 99%
“…Tan & Liu (2015, ix) describe when introducing the publication about teacher effectiveness in our global world that is in continuous changing process: "In this challenging time, we need teachers who inculcate in their students a deep love for learning, and empower then so that they can become self-directed and collaborative learners." Teachers can have wide impact on students' life (Kyriakides, et al 2019) by promoting equality and preventing discrimination.…”
Section: Teachers At An Institution Levelmentioning
confidence: 99%
“…In addition, in a larger class, one-to-one interaction between students and their teacher might be more difficult than in smaller classes. Finally, research on group composition effects should also be considered, especially since statistically negative effects of more language diversity were found (Belfi, Haelermans, & de Fraine, 2016;Kyriakides, Creemers, & Charalambous, 2019). The language contact hypothesis of Driessen (2003) states that students in segregated classes have fewer opportunities to come into contact with the language of instruction when compared to students in classes with a higher proportion of native-speaking students.…”
Section: Identifying Class-level Correlates Of Listening Performancementioning
confidence: 99%